1996
DOI: 10.1152/jappl.1996.81.2.738
|View full text |Cite
|
Sign up to set email alerts
|

Peak ventilatory responses during cycling and swimming in pregnant and nonpregnant women

Abstract: This study was designed to determine whether pregnancy affects peak O2 uptake (VO2peak) during swimming compared with cycling. We studied 11 women at 30-34 wk gestation and 8-12 wk postpartum. We measured heart rate (HR), O2 uptake (VO2), CO2 output (VCO2), minute ventilation (VE), and lactic acid concentration. Peak HR was not significantly affected by the type of exercise or by pregnancy. VO2peak was 9% lower during swimming than during cycling but was not affected by pregnancy, with values for pregnancy cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
(3 reference statements)
5
24
1
5
Order By: Relevance
“…During submaximal non-weight-bearing exercise, the difference in absolute VO 2 (L/min) between pregnant and nonpregnant women is either unchanged or increased during pregnancy. 12,26,[30][31][32][33][34][35][36][37] In contrast, during weight-bearing exercise the absolute VO 2 (L/min) is elevated further and has been suggested to be related to gestational weight gain. However, when these values are expressed relative to body weight (mL/kg/min) oxygen consumption is lower, similar or slightly higher for a given work rate.…”
Section: Energy Expenditure During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…During submaximal non-weight-bearing exercise, the difference in absolute VO 2 (L/min) between pregnant and nonpregnant women is either unchanged or increased during pregnancy. 12,26,[30][31][32][33][34][35][36][37] In contrast, during weight-bearing exercise the absolute VO 2 (L/min) is elevated further and has been suggested to be related to gestational weight gain. However, when these values are expressed relative to body weight (mL/kg/min) oxygen consumption is lower, similar or slightly higher for a given work rate.…”
Section: Energy Expenditure During Pregnancymentioning
confidence: 99%
“…However, maximal exercise testing in pregnancy is rarely conducted as it carries the theoretical risk of compromised blood flow to the fetus. Nonetheless, the few studies that measured maximal oxygen uptake demonstrated that absolute VO 2 (L/min) is unchanged from pregnancy to postpartum or nonpregnant controls during either weight-bearing [32][33][34]39,40 or nonweight-bearing exercise. 39,41 These data suggest that the absolute capacity of the aerobic system remains similar to the nonpregnant state; however, the amount of work that can be done is reduced.…”
Section: Energy Expenditure During Pregnancymentioning
confidence: 99%
“…También se descubre que al realizar un ejercicio con el ciclo ergómetro en ambos medios, parece ser que las demandas para satisfacer el ejercicio en el medio acuático son menores, en cuanto a ritmo cardiaco y elevaciones de la tensión arterial se refiere (Katz, McMurray, Goodwin, & Cefalo, 1990a), añadiendo Sibley, Ruhling, Cameron-Foster, Christensen, & Bolen (1981) que tras un programa acuático se mantiene en los límites normales tal y como afirman también en su investigación Finkelstein, Poli de Figueredo, Lima, Bgeginski, Stein, & Martins (2011). Es en la investigación de Spinnewijn et al (1996) donde los resultados indican que la FC max es igual tanto en ciclismo como en natación durante el embarazo. Lynch, Goodman, Choy, Dawson, Newnham, & McDonald (2007) en su investigación advierten una mejora de la capacidad aeróbica submáxima por los valores adecuados de FC obtenidos a lo largo del programa de entrenamiento en natación durante el embarazo, logrando en mujeres sedentarias anteriormente, aumentar considerablemente las distancias conseguidas.…”
Section: Beneficios Maternos a Nivel Fisiológico Y Antropométricounclassified
“…En cuanto a los niveles de triglicéridos en sangre parece que aumentan con el ejercicio con una tendencia a aumentar conforme avanza el embarazo y concentraciones más bajas de cortisol durante la inmersión y el ejercicio en el medio acuático, a pesar que en reposo aumentan con el embarazo (McMurray et al, 1988a). Es en la investigación de Spinnewijn et al (1996) donde se obtienen resultados que confirman que los niveles de ácido láctico son menores en natación que en ciclismo, así como menores en el embarazo que en el postparto. Son Katz, McMurray, Turnbull, Berry, Bowman, & Cefalo (1990b) los que apuntan en su investigación que Los niveles de prolactina decrecen significativamente con la inmersión, el ejercicio y la recuperación.…”
Section: Beneficios Maternos a Nivel Fisiológico Y Antropométricounclassified
See 1 more Smart Citation